(3GdCOhjI hGdCZPjI GdeaQOIs
(3ChdgG (B:s
(3GdHGH GdKGfi ai GdCOhjI hGdCZPjI GdeaQOI , hbO QJHfGg Ydi MQha CHLO MQa GdCda (B: (3GHQjSe (B: (3eGgjJg eYQhaI , hgh MGQai GdChdi eaQM hNGUI GdNGe s
(3BNQgG (B:s
(3eHJhQ GdBNQ hBNQ GdehLhO efg ef NdGd GdcdGe Ydi (B" (3Ecdjd Gdedc (B" (3hjfaY GdbQhM GdQWHI hGdTgOjI , hgj GdNTfI ef GdbQhM , VeGQG hMOg , Ch eY HYV GdbhGHV s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B12 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdWHs